Spectroscopy-Based Approaches for Microplastic Detection Across Environmental and Biological Matrices: A Mini Review - Khamsiah Ahmad; Yuliana; Muthmainnah; Inayah; Safar Dody (UNIVERSITAS KHAIRUN, 2026)
Microplastic contamination is a global concern due to its widespread occurrence in environmental and biological matrices, including water, sediments, and marine organisms. Accurate detection and characterisation are essential to understand their distribution, sources, and potential risks to ecosystems and human health. This review summarises advances in spectroscopy-based and complementary analytical techniques for microplastic detection, focusing on Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy, confocal laser scanning microscopy (CLSM), scanning electron microscopy (SEM), and pyrolysis–gas chromatography–mass spectrometry (Py-GC-MS). FTIR and Raman spectroscopy remain the primary tools for polymer identification through molecular fingerprinting, while CLSM enables rapid fluorescence-based screening and three-dimensional imaging. SEM provides detailed morphological information, revealing particle surface characteristics and weathering processes. In contrast, Py-GC-MS offers highly sensitive mass-based quantification and identification of polymer composition and associated additives. Each technique has distinct advantages and limitations related to sensitivity, resolution, throughput, and applicability to complex matrices. Therefore, integrated multi-method approaches are increasingly recommended to achieve comprehensive and reliable microplastic assessment. This review highlights current methodological developments and future directions to improve analytical accuracy and standardisation in microplastic research.